Chinese Footwear Imports Subject to Antidumping Measures in Peru, 2017 – 2020 - Castillo-Coronado, Yazmin; Morán Santamaría, Rogger Orlando; Coronel Benites, Cynthia Vanessa; Lizana Guevara, Nikolays Pedro; Arias Gonzales, Hilda Paola; Reaño Gonzáles, Enrique Alberto; Montes Ninaquispe, Jose Carlos (LACCEI, 2024)
The research conducted compared the imports of footwear in Peru affected by antidumping measures and those not affected during the period from 2017 to 2020, aiming to evaluate the resulting trade dynamics and their effect on the footwear industry. Employing a quantitative approach and a non-experimental design, import data under subheading 64.02.99.90.00 were analyzed, comparing imports subject to antidumping measures with those that were not. The results show a decreasing trend in the CIF value of imports without antidumping measures, contrasting with modest growth in the value of imports affected by these measures. Additionally, an increase in the unit value of products subject to antidumping measures was observed, suggesting a significant impact of these policies on the prices and volumes of imports. The study’s conclusions highlight that, although antidumping measures provide temporary protection to the local industry, they also significantly alter market dynamics, affecting both consumers and importers alike. The importance of ongoing monitoring and thorough evaluations to ensure that these measures promote an adequate balance between the protection of the national industry and the benefits derived from international trade is emphasized. As a recommendation, it is suggested that the Peruvian government and relevant entities promote innovation, competitiveness, and the creation of export consortia. These measures aim to improve the competitiveness of the Peruvian footwear industry on a global scale, minimizing dependence on protectionist practices and fostering durable and competitive industrial development in the international context.